Características cefalométricas y antropométricas craneofaciales de los pacientes con síndrome de hiperinmunoglobulinemia E con infecciones recurrentes (SHIEIR) (2002)
ABSTRACT: The purpose of this study that was carried out on patients with Hyperglobulinemia E and Recurrent Infections Syndrome, was to analyze by means of lateral and frontal cephalic x-rays, the common cephalometric characteristics among them. Also, craneofacial anthropometric measurements were made in order to compare them with international standars and in this way define in a more precise way the craneofacial characteristics of these patients Stomatological clinical records, periapical radiographs, panoramic, frontal and lateral head plates, photographs, stone models and anthropometric measurements were taken in eight patients between tha ages of three and twenty one years and with levels of serum inmunoglobulin E higher than 2000 IU/ml, with typical history of SHIEIR (according to WHO criteria). As a common cephalometrical characteristic it was found that all the patients had an increased gonial angle; no severe asymmetries were found that would compromise the patients clinically or in their esthetics. In relation with the anthropometric measurements it was found that there was an increase in the intercantal internal and external distances, nasal width and length in patiens with SHIEIR in the age of growth.